Effect of P, FYM and PSB on Macronutrient Concentration and Uptake by Sunflower - and J.A. Wani, M.A. Malik, Mushtaq A. Wani (Journal of the Indian Society of Soil Science, 2014)
A field experiment was conducted at SKUAST-K, Shalimar to study the effect of P, FYM and PSB on macronutrient concentration and uptake in sunflower. The soil of the experimental site was silty clay loam in texture, non-saline and neutral in reaction. The results revealed that application of P, FYM and PSB resulted in an improvement in the per cent content of N, P, K, Ca, Mg and S in seed and stalk of sunflower. Treatment combination P40FYM10PSB1 was found superior to all other treatments which showed the highest concentration of P in seed (0.30%) and K in stalk (1.41%) of sunflower. Under this treatment combination, uptake of N, P, K, Ca, Mg and S at harvest was highest in grain i.e. 111.5, 11.5, 10.7, 28.3, 10.3 and 10.9 kg ha-1, respectively, whereas that of N, P and Mg was highest in stalk (19.5, 1.21 and 1.14 kg ha-1, respectively).